The priest anointed for battle - Martola, Nils (Nordisk judaistik/Scandinavian Jewish Studies, 1983)
The reason why I undertook to study the theme “The priest anointed for battle” was that while studying texts having to do with the Messiah, Son of Joseph, often called the Anointed for battle § 1 §, I repeatedly came upon rabbinic texts which also dealt with the one Anointed for battle, but which seemed to deal with another person, a priest. Although scholars, who had previously noted this phenomenon were certain that the texts dealt with two different persons having the same title, I felt that the texts should be examined in a more thorough way to determine whether or not there existed an organic relation between the traditions about the two persons. It soon became clear that the texts dealing with the priest Anointed for battle § 2 § exhibit several interesting features, most important being perhaps that the texts are inherently eschatological in character and that the texts dealing with the § 1 § often seem foreign in their respective context.